Comparative Study of Electronic Transaction Criminal Liability and Money Laundering in Binary Option Electronic Trading Transactions - Diah Prasetyowati; Selamat Lumban Gaol; Sujono (International Journal of Science and Society, 2023)
Industry 4.0 or the fourth industrial revolution is a general term used for the level of development of the technology industry in the world. Industry 4.0 describes the growing trend towards automation and data exchange in technology and processes in the manufacturing industry. These trends include the Internet of Things, Industrial Internet of Things, cyber physical systems, artificial intelligence, smart factories, cloud computing systems, and so on. In research for writing this thesis the author uses normative legal research methods (normative juridical) or often also referred to as library research. The provisions of legislation in Indonesia that regulate prohibited acts that become criminal acts of electronic transactions are regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, namely in Articles 27 to Article 37 of the ITE Law Regulations on electronic transaction crimes and money laundering in electronic trading transactions in Indonesian criminal law regulated in Article 27 to Article 37 of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Meanwhile, the laws and regulations governing the crime of money laundering are regulated in Article 3 Jo. Article 4 Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes (UU PP-TPPU).